A study on Romania Sustainable Development. (2015) - Sirbu, Roxana-Mihaela; Popescu, Anca-Diana; Borca, Cristina; Draghici, Anca
Abstract: In the globalization context, the sustainable development becomes a necessity. A sustainable society is characterized by green investments, investments in research, development and innovation, industrial upgrading, update and new skills for existing and new occupations, green and competitive economy development. The purpose of this paper is to analyze the state of sustainable development in Romania through the analysis of statistical data related to indicators for determining the sustainability of Romania (green investments, employment rate, gross domestic expenditure on research, development and innovation, greenhouse gas emissions, share of renewable energy in gross final energy consumption, share of early leavers from education and training, tertiary educational attainment and people at risk of poverty or social exclusion). This paper is part of an extensive research on green investment and their impact on the organization sustainable development, aiming to achieve a conceptual business model and an associated methodology in order to support the decision making process.